Pandangan MUI Kabupaten Langkat Mengenai Mekanisme Kerja Dokter Ahli Kandungan Laki-laki dalam Menangani Wanita Hamil dan Melahirkan (Studi Kasus RSU Mahkota Bidadari Gebang) - Sena Sahputri; As’ad Badar (Peduli Riset dan Pengabdian Masyarakat, 2024)
Observations show that more male obstetricians treat pregnant women than female doctors, which raises ethical and Islamic considerations regarding aurat. This study aims to explore the views of the Indonesian Ulema Council (MUI) of Langkat Regency regarding the work mechanism of male obstetricians in handling pregnant women and giving birth at Mahkota Bidadari Gebang Hospital. The research method used is a qualitative approach with the type of field research and case study, which involves observation, interviews, and documentation as data collection techniques. The results showed that in emergency situations, where there are no female doctors available, male obstetricians are allowed to treat female patients, as long as they adhere to the basic principles of sharia such as maintaining aurat and ensuring there is a companion during the examination. The MUI of Langkat District confirms that under normal conditions, female doctors are the first choice to handle female patients to maintain honour and privacy, but leeway is given in urgent circumstances to ensure the safety and health of patients are maintained in accordance with Islamic values.